Possible benefits of whole goat milk in infant formulas for a healthy baby - O. N. Komarova (Лечащий Врач, 2021)
Goat milk protein-based formulas for feeding babies of the first year of life have been used since the 80s of the last century. A new generation of infant formula is made using whole goat milk, in which the natural ratio of whey protein: casein is maintained at 20:80, milk fat and carbohydrate components are preserved, which allows translating the benefits of goat milk into an adapted formula to approximate the composition of breast milk (BM). Protein and milk fat obtained from whole goat milk are highly digestible due to the structural and compositional characteristics: protein with low αs1-casein forms a soft clot in the stomach, which facilitates its easy diges- tion, and the fat globules of goat milk are smaller and larger surface area comparable to BM. Goat milk fat in the formula is the source of the main donor energy – fatty acids with a short and medium carbon chain length, β-keto acids, and palmitic acid in the sn-2-position in the glycerol molecule. In the composition of the formula during the production process, the goat's milk fat globules membranes (MFGM) are preserved. The components of MFGM have different physiological functions. MFGM proteins contribute to the development of intestinal microbiota, immune functions, have antimicrobial and antiviral effects. Lipids MFGM improve the barrier functions of the intestinal epithelium, maintain its structural integrity, and also participate in the construction of cell membranes of the mucous membrane of the gastrointestinal tract and the rapidly developing nervous tissue of the child. In whole goat milk, oligosaccharides (OS) are present in a smaller amount and variety in comparison with BM, which dictates the need to supplement the infant formula with OS or prebiotics that repeat the functions of BM OG. Clinical studies have shown evidence of the safety and clinical efficacy of using whole goat milk formulas in promoting the proper growth and development of infants in their first months of life.